Elevated IL-13 in effusions of patients with HIV and primary effusion lymphoma as compared with other Kaposi sarcoma herpesvirus-associated disorders. (1st January 2021) - Ramaswami, Ramya; Lurain, Kathryn; Marshall, Vickie Ann; Rupert, Adam; Labo, Nazzarena; Cornejo-Castro, Elena; Miley, Wendell; Wang, Hao-Wei; Widell, Anaida; Lindsley, Matthew; Yuan, Constance; Stetler-Stevenson, Maryalice; et al.
Abstract : Objective: To assess the cytokine and viral profiles of effusions and peripheral blood among patients diagnosed with HIV and Kaposi sarcoma herpesvirus [KSHV, also known as human herpesvirus 8 (HHV-8)]-associated conditions. Design: Retrospective comparative study evaluating clinicopathologic findings in patients with HIV and KSHV-associated conditions presenting with an effusion between 2010 and 2018. Methods: Paired peripheral blood and effusion samples collected at the time of pathological diagnosis of KSHV-associated conditions [Kaposi sarcoma, KSHV-associated multicentric Castleman disease (KSHV-MCD), primary effusion lymphoma (PEL), or KSHV-associated inflammatory cytokine syndrome (KICS)] were evaluated for disease-specific and compartment-specific (effusion vs. blood) characteristics. We assessed 12 cytokines, KSHV viral DNA (KSHV-VL), and Epstein--Barr virus (EBV) viral DNA (EBV-VL). Results: Nine patients had PEL, five patients had KSHV-MCD, and eight patients met criteria for KICS; all but one patient had concurrent Kaposi sarcoma in addition to these conditions. PEL effusions had substantially higher levels of IL-13 (median 16.9 pg/ml; interquartile range 9.7--26.9 pg/ml) compared with KSHV-MCD (median <0.114 pg/ml; P  = 0.0037) or KICS (median <0.114 pg/ml; P  = 0.0003) effusions. IL-13 was also higher in PEL effusions as compared with serum (median <0.12 ng/ml; P  = 0.007). KSHV-VL levels were significantly higher in PEL effusions as compared with KICS effusions (median 31 × 10 6 vs. 569 copies/million-cell equivalent; P  = 0.0005) or KSHV-MCD effusions (median 231, 884 copies/million-cell equivalent; P  = 0.02). Conclusion: PEL effusions had a distinct profile as compared to other KSHV-associated diseases with regard to elevated IL-13 and KSHV-VL. These findings may provide insights into PEL pathogenesis and aid in diagnosis. Abstract : Supplemental Digital Content is available in the text